Rechts- und Staatsphilosophie bei G.W. Leibniz - Altwicker, Tilmann; Cheneval, Francis; Mahlmann, Matthias (Mohr Siebeck, 2020)
G.W. Leibnizs Philosophy of Law and State.
PublicationDate: 20201127
Keywords: Metaphysik -- Erkenntnistheorie -- Logik -- Naturrecht -- Moralphilosophie -- Ehegüterrecht -- Rechtsphilosophie -- Rechtsgeschichte -- Array